The apocalyptic motives in the tetralogy by Viachaslau Adamchyk - Apanasovich, Natallya G. (Journal of the Belarusian State University. Philology, 2020)
The article deals with the apocalyptic moties in the tetralogy by V. Adamchyk (four books, 1977–1990) as the way of artistic expression of the writer’s concept of the tragedy of the Belarusian people’s fate. The interrelationship and interdependence of all forms of the national existence as well as their impact on the fate of the individual and the nation as a whole are shown. The researcher analyzes the existential contradiction of human existence as an agent in their life and as a victim of history revealed in the Western Belarusian context. The peculiarities of the author’s view on the tragic Belarusian fate are presented through the triad sin – atonement – penitence, through an anthropocentric perspective (attention to a person, their daily life, involuntary involvement in historical events). The emphasis is made on the V. Adamchyk’s desire to avoid ambiguity, to comprehend axiological contradictions, to realize the scale of a mental catastrophe during the global conflicts. It is concluded that the narration is set in the Christian context, according to which the fate of the Belarusian is presented as the longsuffering way.